2005
DOI: 10.1093/bja/aei239
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prospective study of biochemical markers and evoked potentials for identifying adverse neurological outcome after thoracic and thoracoabdominal aortic aneurysm surgery

Abstract: TcMEP monitoring during TAA/TAAA surgery seems to be an effective but not completely sufficient guide in our protective multi-modality strategy. Combinations of the serum concentrations of S-100B and tcMEP ratios during the early reperfusion period might be associated with adverse neurological complications. Furthermore, biochemical markers could detect central nervous system injury on the first postoperative day and may have prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…The authors argued that surgical trauma itself may be responsible for serum S100B increments in the absence of central nervous injury. 66 A similar study showed that at 5 and 24 h after operation, S100B was significantly higher in patients who underwent hypothermic circulatory arrest than those who did not undergo circulatory arrest. 67 Furthermore, there was a positive correlation between duration of the circulatory arrest and the postoperative levels of the biomarker.…”
Section: S100b In Non-cardiac Surgerymentioning
confidence: 86%
See 1 more Smart Citation
“…The authors argued that surgical trauma itself may be responsible for serum S100B increments in the absence of central nervous injury. 66 A similar study showed that at 5 and 24 h after operation, S100B was significantly higher in patients who underwent hypothermic circulatory arrest than those who did not undergo circulatory arrest. 67 Furthermore, there was a positive correlation between duration of the circulatory arrest and the postoperative levels of the biomarker.…”
Section: S100b In Non-cardiac Surgerymentioning
confidence: 86%
“…An investigation of the predictive value of NSE from CSF and serum in patients undergoing aortic aneurysm repair concluded that neither NSE nor S100B could replace or add information to the transcranial motor-evoked potentials monitoring during surgery. 66 In a small cohort of patients who had descending thoracic or thoracoabdominal aorta repair, NSE concentrations in the CSF increased in patients with and without neurological symptoms 65 (Table 3). The increase in NSE after internal cardiac defibrillator implantation was associated with impaired attention and memory after operation.…”
Section: Nse In Non-cardiac Surgerymentioning
confidence: 99%
“…2324 Calponin 1 is a regulator of vascular smooth muscle tone and has been shown to be a target of MMP2, 25 whereas S100‐A4 is a calcium signal transducer that has been shown to positively regulate the secretion of MMPs from endothelial cells and fibroblasts and to regulate the transcriptional activation of collagenase 3 (MMP‐13) mRNA followed by subsequent release of MMP protein and the proteolytic degradation of extracellular matrix. 2628 α‐Enolase is a multifunctional protein and is involved in the synthesis of pyruvate but also acts as a plasminogen receptor, where it regulates the activation of plasmin leading to MMP activation and extracellular matrix degradation. 20 CSRP1 is expressed in vascular smooth muscle, and CRP2 is a cofactor for smooth muscle cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have exploited the indwelling spinal drain as a real-time source of potential biochemical markers [5][6][7]. Such markers will generally reflect release from any CNS tissue.…”
Section: Introductionmentioning
confidence: 99%